2011
DOI: 10.1051/0004-6361/201118240
|View full text |Cite
|
Sign up to set email alerts
|

A newα-enhanced super-solar metallicity population

Abstract: We performed a uniform and detailed analysis of 1112 high-resolution spectra of FGK dwarfs obtained with the HARPS spectrograph at the ESO 3.6 m telescope (La Silla, Chile). Most stars have effective temperatures 4700 K ≤ T eff ≤ 6300 K and lie in the metallicity range of −1.39 ≤ [Fe/H] ≤ 0.55. Our main goal is to investigate whether there are any differences between the elemental abundance trends (especially [α/Fe] ratio) for stars of different subpopulations. The equivalent widths of spectral lines are autom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
214
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(238 citation statements)
references
References 43 publications
18
214
2
Order By: Relevance
“…Here we use this dichotomy in the chemical evolution to separate different stellar populations. Adibekyan et al (2011) showed that the stars of this sample fall into two populations, clearly separated in terms of [α/Fe] up to super-solar metallicities. In turn, high-α stars were also separated into two families with a gap in both [α/Fe] Adibekyan et al (2011) to separate the stellar groups 4 .…”
Section: Dissecting the Galactic Disksmentioning
confidence: 87%
See 2 more Smart Citations
“…Here we use this dichotomy in the chemical evolution to separate different stellar populations. Adibekyan et al (2011) showed that the stars of this sample fall into two populations, clearly separated in terms of [α/Fe] up to super-solar metallicities. In turn, high-α stars were also separated into two families with a gap in both [α/Fe] Adibekyan et al (2011) to separate the stellar groups 4 .…”
Section: Dissecting the Galactic Disksmentioning
confidence: 87%
“…It is becoming increasingly clear that a dissection of the Galactic disks based only on stellar abundances is superior to kinematic separation (e.g., Navarro et al 2011;Lee et al 2011;Adibekyan et al 2011;Liu & van de Ven 2012). This is because chemistry is a relatively more stable property of a star than its spatial positions and kinematics.…”
Section: The Sample and Disk Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in [α/Fe] between the thin and thick disc clusters with ages of 4 to 9 Gyr suggest that age cannot be the key variable, but different proportions of Type II to Type Ia supernovae products in clusters formed at dif- Adibekyan et al 2013;Bensby et al 2014). Although the origin of such objects is still in debate, Adibekyan et al (2011Adibekyan et al ( , 2013 have suggested a possible origin of these α-enhanced metal-rich stars in the inner Galaxy (bulge) followed by a subsequent migration to the solar vicinity.…”
Section: [α/Fe] Vs Cluster's Agementioning
confidence: 99%
“…Adibekyan et al 2011;Recio-Blanco et al 2014) and kinematic approaches (e.g. Bensby et al 2003;Reddy et al 2006).…”
Section: Kinematic Propertiesmentioning
confidence: 99%